Digital reality – challenge for vocational education teachers - Mikeladze, Madona; Gogmachadze, Nino (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Technologies have changed the essence of teaching-learning. A modern vocational education teacher needs to effectively navigate the sea of ​​information, obtain and sort the necessary information, create and share new information. This in itself requires the possession of specific digital skills. (Using office programs; managing e-mail; using online learning platforms; using video conferencing tools; creating digital educational resources; integrating digital tools into the learning process, etc.). The paper presents the results of the research on the digital skills of vocational education teachers in Georgia. The research aimed to evaluate the readiness of teachers to use modern technologies in the educational process. The competencies of teachers were investigated in areas such as: creation and use of digital resources, online communication, data analysis and digital security. The results show that the digital skills of vocational education teachers need significant improvement. Both strengths and challenges were identified. The report presents recommendations for the development of professional development programs aimed at improving the digital competencies of teachers.